Stigma and discrimination towards Covid 19 patients and suspects/ Intan Natasha Mustafah ... [et al.] - Intan Natasha, Mustafah; Mohd Nor Junaida, Mardhiyah; Idris, Nurdiyanah; Jaapar, Iqbal; Amairudin, Muhammad Firdaus; Bakar, Mohd Hilmi (Faculty of Communication & Media Studies, 2021)
Stigma generally means contrary sentiments that individuals have about specific conditions or qualities that someone may have. In contrast, discrimination conveys the meaning of treating someone or a particular group in the public arena less decently than others. This study aims to determine the level of stigma and discrimination of the public towards COVID-19 patients and suspects. An online questionnaire with 11 items in the demographic section and 11 items was designed to evaluate the level of both stigma and discrimination. The study involved 404 respondents of Malaysian Citizens who are from different states and demographic backgrounds by using the Google Form platform. The amount of survey calculated based on Krejcie and Morgan Table, N=32 000 000, S=384. This study involved 404 respondents. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis, and the results of the SPSS indicated that most Malaysian citizens do have a stigma towards the COVID-19 patients and suspects rather than discriminate against them by (M=2.07).